A World Café Approach to Exploring Perspectives on Diabetes Stigma in the United Kingdom - Amy Elizabeth Burton; Alison Owen; Jennifer Taylor; Sarah Elizabeth Dean; Rachel Povey (Wiley, 2024)
ABSTRACT Introduction Research has found that a high percentage of people with diabetes experience stigma, with perceptions of stigma being significantly higher among people with Type 1 diabetes compared to those with Type 2 diabetes. These experiences of diabetes stigma can lead to psychological, behavioural and medical consequences. The aim of the current study was to explore the perceptions of diabetes stigma and propose strategies for addressing this from the perspective of key stakeholders. Methods A mixed methods design was used, commencing with an online qualitative survey (n = 128) and followed by a World Café (n = 11), where attendees reflected on their own experiences with stigma and discussed the survey findings. Results The survey indicated that 75% of those with Type 1 diabetes and 51% with Type 2 had experienced diabetes stigma. The World Café identified three main areas that participants felt impacted their experiences with stigma or had the potential to help improve stigma: healthcare interactions, public awareness and media representations. Conclusions The findings supported previous research showing that diabetes stigma is prevalent among people with diabetes. The World Café was an excellent means of sharing knowledge and experiences among stakeholders, the findings of which will inform strategies to bring about change. Patient or Public Contribution World Café is a collaborative method where stakeholders contribute to the production and analysis of data through rounds of discussion and feedback.